How leaders learn : master the habits of the world's most successful people - Novak, David, 1953- (Boston, Massachusetts : Harvard Business Review Press, 2024)
"When you put learning at the center of everything you do, you'll grow your career, boost your leadership skills, enrich your relationships, and increase your joy and fulfillment in life. But even for people who are naturally curious and interested in solving problems, being an effective learner-one who can turn learning into action-takes insight and practice. This collection of wisdom and practical habits from some of the most successful leaders in the world-CEOs from many industries, military and political leaders, sports greats, subject matter experts, and coaches-is your active-learning manual. Chapter by chapter, they'll share how they've climbed to the highest levels in their respective fields. With infectious enthusiasm and optimism, David Novak highlights these leaders and tells his own incredible story. A trailer park kid who lived in twenty-three states before high school, Novak rapidly ascended the ranks at PepsiCo to become cofounder and CEO of one of the largest corporations in the world, the global restaurant icon Yum! Brands (KFC, Taco Bell, Pizza Hut, and The Habit Burger Grill). And he credits active learning with getting him there. Through stories of wins and losses, missteps and miracle saves, challenges tackled, and problems solved, Novak shows you all the ways you can become an active learner. A leadership devotional for the modern age, How Leaders Learn will appeal to any reader looking to be inspired by great leaders and for practical advice with which to emulate their success in work and life"--
Includes index.
Keywords: Leadership -- Case studies; Chief executive officers -- Case studies